Modelo de gestión por procesos para mejorar el desempeño en el área Agri-Food - Delgado Seclén, Juan Gabriel (2020)
This research proposes improvements for the agri-food sector, which presents problems including: complaints from customers, who state that auditors and inspectors do not arrive at agreed-upon times; lack of procedures, which confuses clients since inspectors complete different operations for the same service; and finally, lack of input and output control of stored materials, so material required by all organizational personnel is frequently missing. After explaining the problems in the agri-food sector, this study aims to mitigate these directly-related problems, given that the client currently has a bad impression about the service. Likewise, the investigation was performed on a company that provides inspection, audit, testing and food certification services. The objective of this study is to determine the impact of a business process management model on the performance of the agri-food sector, with the aim of reducing complaints, standardizing activities carried out by the inspectors in the field and accounting for the materials required by all collaborators. The design of this research is time-series quasi-experimental; descriptive and inferential statistics have also been applied. Finally, the results obtained were: reduction of complaints, standardization of fieldwork and order fulfillment, all of which can be seen in the hypothesis testing.